2006
DOI: 10.1227/01.neu.0000232841.08876.da
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Histological and Scanning Electron Microscopy Results of Endovascular and Operative Treatments of Experimentally Induced Aneurysms in the Rabbit

Abstract: This study demonstrates complete and stable aneurysm obliteration with vessel wall reconstruction after clipping, a sufficient obliteration of the aneurysm dome using endovascular techniques, but a failed healing response of the aneurysm neck that might correlate to its associated higher risk of rebleed. Whether or not this is counterbalanced by the better immediate outcome after endovascular treatment remains a matter of debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…68 Many investigators have published scales that offer a rational, if not a validated basis, for assessing the performance of an implant, by giving points for features considered favorable for healing, including neck coverage with neointima, thickness of neointimal layer, or clot organization at the dome. 11,19,[43][44][45][46][47]56,69 These semiquantitative scales have largely been confined to single-center experiences; they have not been reproduced or validated. No one, to our knowledge, has been able to show that these criteria predict better in vivo clinical performances, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Many investigators have published scales that offer a rational, if not a validated basis, for assessing the performance of an implant, by giving points for features considered favorable for healing, including neck coverage with neointima, thickness of neointimal layer, or clot organization at the dome. 11,19,[43][44][45][46][47]56,69 These semiquantitative scales have largely been confined to single-center experiences; they have not been reproduced or validated. No one, to our knowledge, has been able to show that these criteria predict better in vivo clinical performances, however.…”
Section: Discussionmentioning
confidence: 99%
“…8,18,30,31 Microscopic recurrences have been described with the rabbit elastase model, but a correlation with angiographic recurrences is rarely possible. 45,49,50 Nevertheless, characteristics of the healing of experimental aneurysms, mainly gleaned from cross-species comparisons, have been described. These studies have uniformly revealed organization of the thrombus within the aneurysmal sac within 6 months of platinum coil embolization of surgically created aneurysms in canines and swine, as well as neointimal coverage of the ostium of occluded aneurysms.…”
Section: Pathologic Analyses Of Treated Aneurysmsmentioning
confidence: 99%
“…Many researchers focused on "deficient healing," alternatively considered as deficient fibrosis, 5,6 lack of endothelialization, 7 or insufficient neointima formation. 8 Recurrences can be explained, we will argue, without resorting to such concepts.…”
mentioning
confidence: 99%
“…Krings et al 51 tested stent assisted coiling and found that porous stents resulted in higher rates of aneurysm recanalization than covered stents. In addition, Krings et al 52 demonstrated comparable rates of in-stent stenosis with those seen in human aneurysms treated with stent assisted coiling. As mentioned above, the curvature of the parent vessel of the rabbit elastase aneurysm allows for accurate characterization of intra-aneurysm flow dynamics both before and after treatment.…”
Section: Device Testingmentioning
confidence: 89%